Effect of Thickness on Some Optical Properties of Fe2O3 Thin Films Prepared by Chemical Spray Pyrolysis Technique - Noor Al- Huda H. Abd Al-Husain (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The paper reports the influence of the thickness on the some optical properties of Fe2O3 thin films,which were prepared by chemical Spray  pyrolysis technique on glass substrate heated to 400Ëšc.The thickness of thin films (250,280,350)nm were measured by using weighting method. The optical properties include the absorbance and reflectance spectra,extinction coefficient,and real and imaginary part of the dielectric constant.The result  showed that the optical constant(k,Îµr,Îµi)decreased with the increase of the thickness.